PENGARUH OUTDOOR EDUCATION TERHADAP PENURUNAN KECEMASAN SISWA DALAM MENGHADAPI UJIAN NASIONAL - Indra Prabowo; Kardjono Kardjono (Jurnal Educatio, 2017)
AbstractThis study wanted to determine the effect of Outdoor education on reducing anxiety in class IX and high school students in class XII ahead of the National Examination. In this study the samples used for the experimental group were 25 students of class IX in middle school and 18 students in class XII in high school. Outdoor education activities chosen in this study are camping. The research method used was quasi-experimental with The-Static Group Pretest-Posttest Design. Data analysis techniques were performed using parametric statistics which included average difference test (paired sample t-test and independent samples t-test) and gain score using SPSS version 20. The results showed that Outdoor education through camping had an effect on reducing student anxiety in the face of national exams. Based on the average gain value, the decrease in anxiety by the treatment of Outdoor education through camping of junior high school students in the face of the national exam (0.442) is smaller than that of high school students (0.6498)Keyword: Outdoor education, anxiety, National Examination, camping AbstrakPenelitian ini ingin mengetahui pengaruh Outdoor education terhadap penurunan kecemasan siswa SMP kelas IX dan SMA kelas XII menjelang Ujian Nasional. Dalam penelitian ini sampel yang digunakan untuk kelompok eksperimen sebanyak 25 siswa kelas IX SMP dan 18 siswa kelas XII SMA. Kegiatan Outdoor education yang dipilih dalam penelitian ini adalah camping atau berkemah. Metode penelitian yang digunakan adalah kuasi eksperimen dengan bentuk The-Static Group Pretest-Posttest Design. Teknik Analisis data dilakukan menggunakan statistik parametrik yang meliputi uji beda rata-rata (paired sampels  t-test  dan  independent  samples  t-test)  dan  gain  score  dengan  menggunakan bantuan SPSS versi 20. Hasil penelitian menunjukkan bahwa Outdoor education melalui camping berpengaruh terhadap penurunan kecemasan siswa dalam menghadapi ujian nasional. Berdasarkan nilai gain rata-rata, penurunan kecemasan oleh perlakuan Outdoor education melalui camping siswa SMP dalam menghadapi ujian nasional (0,442) lebih kecil daripada siswa SMA (0,6498).Kata Kunci: Outdoor education, kecemasan, Ujian Nasional, camping